MENINGKATKAN KETERAMPILAN BERBICARA (SPEECH DELAY) PADA ANAK USIA DINI DENGAN METODE BERNYANYI DI PAUD FARHANY KHAIR - Syifaushudur Harefa; Mara Untung Ritonga; Wisman Hadi (JURNAL ILMIAH NUSANTARA, 2025)
This study is a qualitative descriptive research aimed at analyzing and describing strategies for handling children with speech delay through the implementation of the singing method at PAUD Farhany Khair. The research method employed is field research with a qualitative descriptive approach, allowing the researcher to gain an in-depth understanding of the phenomenon being studied. The research subjects include the school principal, parents of children with speech delay, and educators involved in the learning process. Data collection was conducted through in-depth interviews and participatory observations to obtain comprehensive information. The results of this study indicate that the singing method can be an effective strategy for stimulating language development in children with speech delay. This method helps enhance children's attention, verbal responses, and engagement in communication, thereby positively impacting their speech development.